The Effectiveness Of Slot Substitution In Improving The Vocabulary For The Eighth Grade Students OF SMP Negeri 4 Mengkendek (LPPM UKI Toraja, 2017)
The objective of the research is to find out the effectiveness of slot substitution in improving vocabulary for the eighth grade students of SMP Negeri 4 Mengkendek. This research used quantitative research. It is to find achievement of mean score of pretest and posttest for the eighthh grade students of SMP Negeri 4 Mengkendek in improving vocabulary. The instrument of the research written test. The population of this research is the eighthh grade students of SMP Negeri 4 Mengkendek academic year 2013/2014 The total of population is 85 students and taken 24 students as sample through random sampling technique. The result of data analysis which is found out through written test that the mean score of pretest is 59.58 and the mean score of posttest is 74.17 (gain scrore 1,69). It means that slot substitution is effective to improve students’ vocabulary at SMP Negeri 4 Mengkendek or hypothesis is accepted.